1988
DOI: 10.1002/jez.1402470112
|View full text |Cite
|
Sign up to set email alerts
|

Reversing cytoplasmic flow in nucleated, constricted sand dollar eggs

Abstract: The purpose of this investigation was to study the nature of the immediate response of the surface to the mitotic apparatus in sand dollar (Echinarachnius parma) eggs. The normal geometrical relationship was changed by snaring fertilized eggs between opposed, overlapping hooks and constricting the eggs to reshape them into two partial spheres joined by a constricted neck about 27 Fm in diameter. When both asters of the mitotic apparatus lay on the same side of the constriction, cytoplasm flowed out of the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The actin cytoskeleton of many embryos, including C. elegans (Strome, 1986) and Boltenia, an ascid-ian (unpublished observations), resembles what we have described in Drosophila: a dense granular cortical layer and a less dense fibrous network extending into the cytoplasm. Cytoplasmic streaming has also been documented in these and other embryos (Hird and White, 1993;Rappaport and Rappaport, 1988; our unpublished observations). Taylor and colleagues have demonstrated the application of solationcontraction coupling not only to amoeba but also to motility of cultured mammalian cells, and have shown that actin polymerizes into a network near the periphery of the interphase cell and disassembles in the vicinity of the nucleus (Kolega et al, 1991;Giuliano and Taylor, 1994).…”
Section: A Working Hypothesis Of Axial Expansionsupporting
confidence: 66%
“…The actin cytoskeleton of many embryos, including C. elegans (Strome, 1986) and Boltenia, an ascid-ian (unpublished observations), resembles what we have described in Drosophila: a dense granular cortical layer and a less dense fibrous network extending into the cytoplasm. Cytoplasmic streaming has also been documented in these and other embryos (Hird and White, 1993;Rappaport and Rappaport, 1988; our unpublished observations). Taylor and colleagues have demonstrated the application of solationcontraction coupling not only to amoeba but also to motility of cultured mammalian cells, and have shown that actin polymerizes into a network near the periphery of the interphase cell and disassembles in the vicinity of the nucleus (Kolega et al, 1991;Giuliano and Taylor, 1994).…”
Section: A Working Hypothesis Of Axial Expansionsupporting
confidence: 66%
“…Rappaport and Rappaport (1988) found that when microtubule asters are trapped within a starfish embryo constricted into a dumbbell shape, flow moves away from the half of the embryo containing the asters. They concluded that the half containing the asters was more contractile and squeezed cytoplasm into the other half (Rappaport and Rappaport, 1988;Rappaport, 1996). Hird and White (1993), on the other hand, found that, in Caenorhabditis elegans embryos treated with nocodazole to create a diminutive aster near the cortex, cortical flow of F-actin moved away from the aster.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies of flow patterns after microtubule manipulation reached opposite conclusions. Rappaport and Rappaport (1988) found that when microtubule asters are trapped within a starfish embryo constricted into a dumbbell shape, flow moves away from the half of the embryo containing the asters. They concluded that the half containing the asters was more contractile and squeezed cytoplasm into the other half (Rappaport and Rappaport, 1988;Rappaport, 1996).…”
mentioning
confidence: 99%
“…Such convincing studies from Echinoderm eggs have led to a general view that the spindle poles represent the key cleavage plane determinant in all animal cells (for reviews see Mabuchi, 1986;Rappaport, 1991). Furthermore, as the spindle poles are distant from the cortex, the anaphase astral microtubulesrare proposed to transmit the cleavage signal to the cortex (Schroeder, 1981;White and Borisy, 1983;Rappaport and Rappaport, 1988;Harris and Gewalt, 1989;Devore et al, 1989;Rappaport, 1991).…”
mentioning
confidence: 99%